Toward a Diversified Knowledge-Based Economy : Education in the Gulf Cooperation Countries Engagement Note - World Bank Group (World Bank, Washington, DC, 2018)
This engagement note provides education sector policymakers with an overview of the status of education across the six Gulf Cooperation Council (GCC) countries and offers insight into the World Bank’s strategies and approaches to supporting education reform in the GCC region. While the Gulf countries are similar in many ways, each country has its own contextual factors and socioeconomic dynamic that may affect the process of education reform. The insights offered build on the similarities and national human development ambitions of each country to offer broad approaches to education reform. Keeping this in mind, country engagements will require further refinements and tailoring to the needs of each GCC country. The note includes an overview of the socioeconomic context and challenges, along with a section on policy interventions within the education sector. It concludes with a discussion of priority areas for the sector, as well as potential strategies for World Bank support to education reform in the GCC.